Infant feeding practices among HIV-positive mothers at Tembisa hospital, South Africa - Armelia Chaponda; Daniel T. Goon; Muhammad E. Hoque (AOSIS, 2017)
Background: Despite the nutritional, physiological and emotional benefits of breastfeeding, HIV-positive mothers cannot practise exclusive breastfeeding for six months because of a range of influences on their feeding choice - thereby creating a caveat for morbidity in infants. Aim: This study explored factors influencing the infant feeding choice of HIV-positive mothers at a peri-urban hospital in Tembisa, South Africa. Methods: This study was qualitative and was conducted among 30 purposefully selected postnatal HIV-positive mothers at Tembisa hospital, Gauteng, from May to June 2011. In-depth interviews were conducted mainly in isiZulu and Sepedi which were then transcribed into English. An open coding system of analysis was used for thematic analysis. Results: Nurses significantly influenced the feeding choices of new mothers - sometimes with inconsistent information. The grandmothers of infants also influenced the new mothers' feeding options, in some cases with the new mother coming under duress. Other relatives like the sisters and aunts of mothers appeared to significantly affect feeding choices. The time frames expressed for the initiation of a supplementary diet were as follows: before 1 month, at 1 month and at 4 months. The main reason was the belief that infants required more than breast milk as sustenance during this period. Conclusion: In the postnatal hospital setting of this study, the feeding choices of mothers were influenced by nursing personnel. Nursing personnel could marry the influential 'authority' they have with correct and consistent information, in order to change feeding behaviour. Significant 'others' like grandmothers and other relatives also influenced decisions on infant feeding. As such, family dynamics need to be considered when encouraging breastfeeding.